(untitled) (Research, Society and Development, 2021)
The fast dissemination of COVID-19 has attracted worldwide attention since its emergence. Therefore, some strategies were adopted to contain the development of the disease, such as social distancing and isolation, but these measures caused physical and psychosocial consequences, especially for adolescents, whose daily lives were completely changed. To identify the number of cases of COVID-19 in adolescents in the municipalities that make up the "calha Norte" of the state of Pará; to describe the prevalence per 100 adolescents. Bibliographic documentary research, with a quantitative and qualitative approach carried out through data collection in the Ministry of Health and Secretary of Public Health of the state of Pará, as well as in the databases: Scielo, Lilacs, PubMed, Google Scholar and Periodics CAPES. We collected the number of cases reported by municipalities between April 3, 2020 and September 12, 2021, among the age group 12 to 19 years, gender and prevalence. It was found that among the municipalities analyzed Oriximiná had the highest prevalence, however Terra Santa and Prainha had the lowest prevalence. Ten studies on the impact caused in the lives of adolescents during the pandemic period were analyzed. The study met the established objectives. To discuss the prevalence and the impacts that occurred during this period was of great relevance in terms of scientific knowledge. More epidemiological studies covering adolescent health and field research focused on this public are suggested, which will certainly contribute to the creation of public policies and to the enrichment of the scientific acquis.